Temporal appearance of opsonizing antibody to Francisella tularensis: detection by a radiometabolic assay. - Canonico, P G (1975)
The burst in oxidative metabolism that is mediated through activation of the hexose monophosphate shunt and accompanies particle ingestion by polymorphonuclear leukocytes was used as the indicator in an in vitro radiometabolic assay for detection of specific opsonizing antibody to Francisella tularensis. Release of 14CO2 from radiolabeled glucose was increased significantly when specific immune serum added to suspensions of monkey polymorphonuclear leukocytes and F. tularensis. With this method, opsonizing antibodies to F. tularensis were detected in monkey serum 3 days after vaccination. Significantly increased opsonic activity in these monkeys preceded the appearance of, and persisted longer than, antibody activity as determined by conventional serological techniques. In addition, sera from 11 of 12 humans that were immunized 1 month to 13 years previously and had nondiagnostic agglutinating antibody titers demonstrated significant opsonizing activity.